Adjusting the length of supramolecular polymer bottlebrushes by top-down approaches - Klein, Tobias; Gruschwitz, Franka V.; Kuchenbrod, Maren T.; Nischang, Ivo; Hoeppener, Stephanie; Brendel, Johannes C. (Beilstein Journal of Organic Chemistry, 2021)
Controlling the length of one-dimensional (1D) polymer nanostructures remains a key challenge on the way toward the applications of these structures. Here, we demonstrate that top-down processing facilitates a straightforward adjustment of the length of polyethylene oxide (PEO)-based supramolecular polymer bottlebrushes (SPBs) in aqueous solutions. These cylindrical structures self-assemble via directional hydrogen bonds formed by benzenetrisurea (BTU) or benzenetrispeptide (BTP) motifs located within the hydrophobic core of the fiber. A slow transition from different organic solvents to water leads first to the formation of µm-long fibers, which can subsequently be fragmented by ultrasonication or dual asymmetric centrifugation. The latter allows for a better adjustment of applied shear stresses, and thus enables access to differently sized fragments depending on time and rotation rate. Extended sonication and scission analysis further allowed an estimation of tensile strengths of around 16 MPa for both the BTU and BTP systems. In combination with the high kinetic stability of these SPBs, the applied top-down methods represent an easily implementable technique toward 1D polymer nanostructures with an adjustable length in the range of interest for perspective biomedical applications.
Keywords: distribution; dual centrifugation; filomicelles; self-assembly; ultrasonication

(untitled) - Truong, N. P.; Whittaker, M. R.; Mak, C. W.; Davis, T. P. (Expert Opin. Drug Delivery, 2015)

(untitled) - Toy, R.; Peiris, P. M.; Ghaghada, K. B.; Karathanasis, E. (Nanomedicine (London, U. K.), 2014)

(untitled) - Liu, Y.; Tan, J.; Thomas, A.; Ou-Yang, D.; Muzykantov, V. R. (Ther. Delivery, 2012)

(untitled) - Müllner, M. (Macromol. Chem. Phys., 2016)

(untitled) - Truong, N. P.; Quinn, J. F.; Whittaker, M. R.; Davis, T. P. (Polym. Chem., 2016)

Frontiers of Nanoscience - Shkodra-Pula, B.; Vollrath, A.; Schubert, U. S.; Schubert, S. (Polymer-based nanoparticles for biomedical applications, 2020)

(untitled) - Gilroy, J. B.; Gädt, T.; Whittell, G. R.; Chabanne, L.; Mitchels, J. M.; Richardson, R. M.; Winnik, M. A.; Manners, I. (Nat. Chem., 2010)

(untitled) - Finnegan, J. R.; Pilkington, E. H.; Alt, K.; Rahim, M. A.; Kent, S. J.; Davis, T. P.; Kempe, K. (Chem. Sci., 2021)

(untitled) - Finnegan, J. R.; He, X.; Street, S. T. G.; Garcia-Hernandez, J. D.; Hayward, D. W.; Harniman, R. L.; Richardson, R. M.; Whittell, G. R.; Manners, I. (J. Am. Chem. Soc., 2018)

(untitled) - He, Y.; Eloi, J.-C.; Harniman, R. L.; Richardson, R. M.; Whittell, G. R.; Mathers, R. T.; Dove, A. P.; O’Reilly, R. K.; Manners, I. (J. Am. Chem. Soc., 2019)

(untitled) - Street, S. T. G.; He, Y.; Jin, X.-H.; Hodgson, L.; Verkade, P.; Manners, I. (Chem. Sci., 2020)

(untitled) - Niederberger, A.; Pelras, T.; Manni, L. S.; FitzGerald, P. A.; Warr, G. G.; Müllner, M. (Macromol. Rapid Commun., 2021)

(untitled) - Müllner, M.; Yang, K.; Kaur, A.; New, E. J. (Polym. Chem., 2018)

(untitled) - Müllner, M.; Mehta, D.; Nowell, C. J.; Porter, C. J. H. (Chem. Commun., 2016)

(untitled) - Müllner, M.; Müller, A. H. E. (Polymer, 2016)

(untitled) - Müllner, M.; Dodds, S. J.; Nguyen, T.-H.; Senyschyn, D.; Porter, C. J. H.; Boyd, B. J.; Caruso, F. (ACS Nano, 2015)

(untitled) - Gruschwitz, F. V.; Klein, T.; Catrouillet, S.; Brendel, J. C. (Chem. Commun., 2020)

(untitled) - Klein, T.; Ulrich, H. F.; Gruschwitz, F. V.; Kuchenbrod, M. T.; Takahashi, R.; Hoeppener, S.; Nischang, I.; Sakurai, K.; Brendel, J. C. (Macromol. Rapid Commun., 2021)

(untitled) - Gruschwitz, F. V.; Fu, M.-C.; Klein, T.; Takahashi, R.; Higashihara, T.; Hoeppener, S.; Nischang, I.; Sakurai, K.; Brendel, J. C. (Macromolecules, 2020)

(untitled) - Klein, T.; Ulrich, H. F.; Gruschwitz, F. V.; Kuchenbrod, M. T.; Takahashi, R.; Fujii, S.; Hoeppener, S.; Nischang, I.; Sakurai, K.; Brendel, J. C. (Polym. Chem., 2020)

(untitled) - Gruschwitz, F. V.; Klein, T.; Kuchenbrod, M. T.; Moriyama, N.; Fujii, S.; Nischang, I.; Hoeppener, S.; Sakurai, K.; Schubert, U. S.; Brendel, J. C. (ACS Macro Lett., 2021)

(untitled) - Maeda, H. (Adv. Drug Delivery Rev., 2015)

(untitled) - Maeda, H.; Nakamura, H.; Fang, J. (Adv. Drug Delivery Rev., 2013)

(untitled) - Krämer, W.; Schubert, R.; Massing, U. (Int. J. Pharm., 2019)

(untitled) - Hagedorn, M.; Liebich, L.; Bögershausen, A.; Massing, U.; Hoffmann, S.; Mende, S.; Rischer, M. (Int. J. Pharm., 2019)

(untitled) - Hagedorn, M.; Bögershausen, A.; Rischer, M.; Schubert, R.; Massing, U. (Int. J. Pharm., 2017)

(untitled) - Hirsch, M.; Ziroli, V.; Helm, M.; Massing, U. (J. Controlled Release, 2009)

(untitled) - Massing, U.; Cicko, S.; Ziroli, V. (J. Controlled Release, 2008)

(untitled) - Krieg, E.; Bastings, M. M. C.; Besenius, P.; Rybtchinski, B. (Chem. Rev., 2016)

(untitled) - Gädt, T.; Ieong, N. S.; Cambridge, G.; Winnik, M. A.; Manners, I. (Nat. Mater., 2009)

(untitled) - Rho, J. Y.; Cox, H.; Mansfield, E. D. H.; Ellacott, S. H.; Peltier, R.; Brendel, J. C.; Hartlieb, M.; Waigh, T. A.; Perrier, S. (Nat. Commun., 2019)

(untitled) - Steinlein, C.; Kreger, K.; Schmidt, H.-W. (Macromol. Mater. Eng., 2019)

(untitled) - Guérin, G.; Wang, H.; Manners, I.; Winnik, M. A. (J. Am. Chem. Soc., 2008)

(untitled) - Peltonen, L.; Hirvonen, J. (J. Pharm. Pharmacol., 2010)

(untitled) - Lamour, G.; Nassar, R.; Chan, P. H. W.; Bozkurt, G.; Li, J.; Bui, J. M.; Yip, C. K.; Mayor, T.; Li, H.; Wu, H.; Gsponer, J. A. (Biophys. J., 2017)

(untitled) - Huang, Y. Y.; Knowles, T. P. J.; Terentjev, E. M. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Nguyen, T. Q.; Liang, Q. Z.; Kausch, H.-H. (Polymer, 1997)

(untitled) - Hennrich, F.; Krupke, R.; Arnold, K.; Rojas Stütz, J. A.; Lebedkin, S.; Koch, T.; Schimmel, T.; Kappes, M. M. (J. Phys. Chem. B, 2007)

(untitled) - Paparcone, R.; Buehler, M. J. (Biomaterials, 2011)